STUDY ON BIOCHEMICAL AND NUTRITIVE VALUE OF POPPED FOXTAIL MILLET - S.GURUPAVITHRA; A.JAYACHITRA; K.DILNA (International Journal of Pharma and Bio Sciences, 2013)
Millets are rich source of nutrients and it was taken as food by the economically weaker section in the world. Popping is a simple processing technique to prepare ready to eat products. Fox tail millet (setaria Italica) is one type of minor millet are popped by mechanical process and used for the production of different snack foods. Foxtail millet have sulphur- containing aminoacids like tryptophan-0.99, threonine-3.10, isoleucine-7.60, leucine-16.06, lysine-2.10, methionine-2.80, phenyl alanine-6.70, valine-6.90, arginine-3.60 and histidine-2.10. In this study, the popping of millet with different pretreatment with sugar, sodium chloride, citric acid and control with water. Then the dried grains were popped in mechanical popper and the popped grain is used for different analysis such as physical and chemical analysis. The Physical characters like moisture, acidity, porosity, rapid viscosity, popped , unpopped, volume, length, breadth and Chemical characters like fat, carbohydrate, crude fiber, amylose, protein, starch, free fatty acid were analyzed from the popped foxtail millet. Then isolate the bacterial colonies were undergone for microbial load analysis such as TNTC, TLTC . The presence of carbohydrate, starch and amylase were analyzed from the prepared Starch cake food and health drink.